PENGARUH KUALITAS, HARGA, DAN CITRA PRODUK TERHADAP KEPUASAN DAN LOYALITAS REMAJA PENGGUNA EMINA DI BALI - PRATIWI, KADEK ANDRIANI DWI; GANDHIADI, G.K.; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika, 2022)
Customer satisfaction in using cosmetic products is influenced by many factors. Emina Cosmetics is one of the local cosmetic products that is well known to the public because the products produced are safe and reliable so that it can create customer satisfaction and affect customer loyalty to continue using these cosmetic products. The purpose of this study was to determine the effect of quality, price, and product image on satisfaction and loyalty of Emina cosmetic users. This study uses a variant-based structural equation model (PLS-SEM). The latent variable in this study is customer satisfaction which is explained by product quality, price, and product image as well as customer loyalty. Data were obtained from 120 female adolescent respondents in Bali Province in each district/city. Based on PLS-SEM, showed that the quality, price, and image of the product affected customer satisfaction by of 77,2%, and customer satisfaction affected customer loyalty in using Emina Cosmetic products by 42,5%.